Strength training: Isometric training at a range of joint angles versus dynamic training - Folland, J. P.; Hawker, K.; Leach, B.; Little, T.; Jones, D. A. (Journal of Sports Sciences, 2005)
Strength training with isometric contractions produces large but highly angle-specific adaptations. To contrast the contractile mode of isometric versus dynamic training, but diminish the strong angle specificity effect, we compared the strength gains produced by isometric training at four joint angles with conventional dynamic training. Thirty-three recreationally active healthy males aged 18?-?30 years completed 9 weeks of strength training of the quadriceps muscle group three times per week. An intra-individual design was adopted: one leg performed purely isometric training at each of four joint angles (isometrically trained leg); the other leg performed conventional dynamic training, lifting and lowering (dynamically trained leg). Both legs trained at similar relative loads for the same duration. The quadriceps strength of each leg was measured isometrically (at four angles) and isokinetically (at three velocities) pre and post training. After 9 weeks of training, the increase in isokinetic strength was similar in both legs (pooled data from three velocities: dynamically trained leg, 10.7%; isometrically trained leg, 10.5%). Isometric strength increases were significantly greater for the isometrically trained leg (pooled data from four angles: dynamically trained leg, 13.1%; isometrically trained leg, 18.0%). This may have been due to the greater absolute torque involved with isometric training or a residual angle specificity effect despite the isometric training being divided over four angles.